980MPa-grade continuous annealing dual-phase steel with low cost and high reaming performance
By optimizing the chemical composition and process flow, the problem of low-cost production of 980MPa continuous retreat dual-phase steel with high hole expansion performance in the existing technology has been solved, and low-cost, high-performance material production has been achieved.
Patent Information
- Application Number
- CN202411604526.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to produce 980MPa grade continuous retardation dual-phase steel with high hole expansion performance at low cost, and the existing continuous annealing units cannot achieve high cooling speed and reheating functions, which limits the improvement of the performance of the material.
By optimizing chemical composition and process process, the low -cost high -pore expansion performance 980MPA -level double -phase steel. Specific measures include: adjust the content of elements such as C, Si, MN, CR, reduce the use of elements such as NB, Ti, and B, and continuously anneal with three -stage hierarchical heating and three -stage cooling process.
It has achieved the production of 980MPa grade continuous retreat dual-phase steel with high hole expansion performance at low cost, improving the material's yield strength, tensile strength and hole expansion rate, while reducing alloy costs.
Smart Images

Figure CN119351879A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cold-rolled strip production, and in particular relates to a 980MPa grade continuous annealing dual-phase steel suitable for producing low-cost and high-hole expansion performance by adopting a continuous annealing unit. Background Art
[0002] The development trend of the modern automobile industry is to reduce fuel consumption and emissions as much as possible while ensuring safety performance. Dual-phase steel has advantages such as good strength and plasticity and high work hardening rate, and has become one of the most widely used advanced high-strength steels. Hole expansion performance (flange extension performance) is an important indicator of the material. It reflects the local deformation of the material and is used to measure the ability of parts to withstand deformation during flanging and hole expansion.
[0003] In the prior art, a higher Mo content is generally added, which leads to a significant increase in alloy cost, and a higher Nb+Ti content makes the hot-rolled strength of the strip higher, which requires a higher load on the cold rolling unit; although Ca treatment can modify the inclusions, it will lead to a significant increase in process difficulty and cost. At the same time, the prior art does not describe the hole expansion rate and uniform elongation, which is not conducive to understanding the overall forming and local forming performance of the product. The prior art uses water to rapidly cool the strip during continuous annealing. Conventional continuous annealing units all use gas cooling, which cannot achieve such a high cooling rate and does not have a reheating function. This method is also not easy to promote on conventional continuous annealing units.
[0004] Therefore, how to prepare low-cost dual-phase steel with high hole expansion performance and high safety performance has become a difficult problem that needs to be solved urgently. Summary of the invention
[0005] Based on this, in order to overcome the deficiencies of the above-mentioned prior art, a method for producing a low-cost, high-hole expansion performance 980MPa grade continuous annealing dual-phase steel using a continuous annealing unit is provided.
[0006] In order to achieve the above purpose, the following technical solutions are adopted: The invention provides a low-cost, high-hole expansion performance 980MPa grade continuously annealed dual-phase steel. The chemical composition of the dual-phase steel comprises, by weight percentage, C: 0.060%-0.095%, Si: 0.30%-0.80%, Mn: 1.95%-2.45%, Cr: 0.55%-0.85%, Nb: 0.010%-0.030%, Ti: 0.020%-0.060%, Cu: 0.020%-0.10%, P≤0.016%, S≤0.012%, Als: 0.02%-0.07%, N≤0.0060%, B: 0.0010%-0.0040%, and the remaining elements are Fe and inevitable impurities.
[0007] In some embodiments, the low-cost and high-hole expansion performance 980 MPa grade continuously annealed dual-phase steel comprises, by weight percentage, the chemical composition of the dual-phase steel includes: C: 0.070%~0.090%, Si: 0.40%~0.55%, Mn: 2.00%~2.25%, Cr: 0.60%~0.80%, Nb: 0.015%~0.025%, Ti: 0.040%~0.055%, Als: 0.028%~0.060%, Cu: 0.030%~0.080%, P≤0.012%, S≤0.008%, N≤0.0035%, B: 0.0020%~0.0035%, and the balance is Fe and unavoidable impurities.
[0008] In some embodiments, the microstructure of the dual-phase steel is composed of 42%-47% ferrite, 30%-35% martensite and 18%-28% tempered martensite, and the yield strength is 668-746 MPa, the tensile strength is 983-1035 MPa, and the total elongation A is 80 The value is 11.0%~14.5%, the uniform elongation is 7.5%~12.0%, the yield strength ratio is 0.64-0.76, and the hole expansion rate is 35%~50%; the average grain size of the ferrite matrix is 1.6μm, the average grain size of the martensite is 1.0μm, and the average grain size of the tempered martensite is 1.2μm.
[0009] The present invention also provides a method for preparing 980MPa grade continuously annealed dual-phase steel with low cost and high hole expansion performance, comprising the following steps: a. Smelting process: smelting the raw materials of duplex steel and forming slabs through continuous casting; b. Hot rolling process: The slab is subjected to heating, descaling, rough rolling, finish rolling and laminar cooling to obtain a hot rolled coil; c. Pickling process: After the hot-rolled coil is pickled, it is formed into a hot-rolled coil, and then cold-rolled into a thin strip steel of 0.8-2.0 mm; wherein, the cold-rolling reduction rate is 43%-68%; d. Continuous annealing process: The cold-rolled thin strip steel is continuously annealed to obtain low-cost, high-hole expansion performance 980MPa grade continuous annealing dual-phase steel; wherein the cold-rolled thin strip steel includes a three-stage graded heating and a three-stage cooling process; wherein the three-stage cooling process includes: the annealing temperature is 805-845°C, first slowly cooled to 660-680°C at 1.7-7.8°C / s, then quickly cooled to 250-290°C at 19-33°C / s, and finally cooled to room temperature.
[0010] In some embodiments, in step b, the final rolling temperature is 845°C-915°C.
[0011] In some embodiments, in step b, the laminar cooling adopts a front-stage cooling method, the cooling rates of the upper and lower surfaces are 40%-60% and 65%-85% respectively, and the coiling temperature is 525-565°C.
[0012] In some embodiments, in step d, the unit speed is controlled at 95-135 m / min according to the thickness of the strip steel; wherein, for every 0.3 mm increase in the thickness of the strip steel, the unit speed is reduced by 10 m / min.
[0013] In some embodiments, in the step a, the following raw materials of dual-phase steel are smelted: in terms of weight percentage, the chemical composition of the dual-phase steel includes: C: 0.060%~0.095%, Si: 0.30~0.80%, Mn: 1.95%~2.45%, Cr: 0.55~0.85%, Nb: 0.010~0.030%, Ti: 0.020~0.060%, Cu: 0.020~0.10%, P≤0.016%, S≤0.012%, Als: 0.02%~0.07%, N≤0.0060%, B: 0.0010%~0.0040%, and the remaining elements are Fe and unavoidable impurities.
[0014] In some embodiments, in step d, the three-stage graded heating process includes: the first stage is a preheating stage with an outlet temperature of 300°C; the second stage is a heating stage, heating the strip to 720°C; the third stage is a heating stage 2, heating the strip to 805-845°C.
[0015] In some embodiments, in step d, the flattening elongation ranges from 0.25 to 0.45%, and the flattening elongation decreases by 0.05% for every 0.3 mm increase in the thickness of the dual-phase steel.
[0016] The present invention has the following beneficial technical effects: The low-cost, high-hole expansion performance 980MPa grade continuous annealing dual-phase steel and preparation method disclosed by the present invention use a relatively low C content (0.060-0.095%) to reduce the hardenability of martensite, so that the hardness difference between the soft phase (ferrite) and the hard phase (ferrite) is reduced, the interphase debonding tendency and the tendency of martensite to crack are reduced, and the hole expansion performance is improved. The addition of a small amount of Cu (0.020-0.10%) not only enhances the effect of aging hardening ferrite, but also inhibits the excessive growth of TiN and TiC, thereby reducing the damage to plasticity and toughness, and also expands the austenite phase region. Relatively cheap elements such as Mn and Cr are used to improve hardenability and ensure strength, and an appropriate amount of Si elements not only promotes the diffusion of C into austenite but also solid solution strengthens ferrite, thereby reducing costs. The addition of a small amount of Nb, Ti, and B elements inhibits the generation of ferrite and increases the recrystallization temperature, and the effectively refined organization improves the hole expansion performance.
[0017] The low-cost and high-hole expansion performance 980MPa grade continuous annealing dual-phase steel disclosed in the present invention has a yield strength of 668-746MPa, a tensile strength of 983-1035MPa, and a total elongation A 80 The value is 11.0%~14.5%, the uniform elongation is 7.5%~12.0%, the yield strength ratio is 0.64-0.76, and the hole expansion rate is 35%~50%; its structure is composed of 42%-47% ferrite (average grain size is 1.6μm), 30%-35% martensite (average grain size is 1.0μm) and 18%-28% tempered martensite (average grain size is 1.2μm). BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 This is a metallographic diagram of a low-cost, high-hole-expansion-performance 980MPa grade continuously annealed dual-phase steel according to an embodiment of the present invention; Figure 2 This is a scanning electron microscope image of a low-cost, high-hole-expansion-performance 980MPa grade continuously annealed dual-phase steel according to an embodiment of the present invention; Figure 3 This is a stress-strain curve diagram of the low-cost and high hole expansion performance 980MPa grade continuously annealed dual-phase steel according to an embodiment of the present invention. DETAILED DESCRIPTION
[0020] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.
[0021] It should be understood that the embodiments of the present invention shown in the exemplary embodiments are only illustrative. Although only a few embodiments are described in detail in the present invention, it is easy for those skilled in the art to appreciate that multiple modifications are feasible without actually departing from the teaching of the subject matter of the present invention. Accordingly, all such modifications should be included within the scope of the present invention. Without departing from the gist of the present invention, other replacements, modifications, changes and deletions may be made to the design, operating conditions and parameters of the following exemplary embodiments.
[0022] Based on the above purpose, a first aspect of an embodiment of the present invention provides a low-cost, high-hole expansion performance 980 MPa grade continuously annealed dual-phase steel, wherein the chemical composition of the dual-phase steel includes, by weight percentage, C: 0.060%~0.095%, Si: 0.30~0.80%, Mn: 1.95%~2.45%, Cr: 0.55~0.85%, Nb: 0.010~0.030%, Ti: 0.020~0.060%, Cu: 0.020~0.10%, P≤0.016%, S≤0.012%, Als: 0.02%~0.07%, N≤0.0060%, B: 0.0010%~0.0040%, and the remaining elements are Fe and unavoidable impurities.
[0023] In a preferred embodiment, the low-cost and high-hole expansion performance 980MPa grade continuously annealed dual-phase steel, in terms of weight percentage, has a chemical composition comprising: C: 0.070% to 0.090%, Si: 0.40% to 0.55%, Mn: 2.00% to 2.25%, Cr: 0.60% to 0.80%, Nb: 0.015% to 0.025%, Ti: 0.040% to 0.055%, Als: 0.028% to 0.060%, Cu: 0.030% to 0.080%, P≤0.012%, S≤0.008%, N≤0.0035%, B: 0.0020% to 0.0035%, and the balance is Fe and unavoidable impurities.
[0024] The microstructure of dual-phase steel is composed of 42%-47% ferrite, 30%-35% martensite and 18%-28% tempered martensite. Its yield strength is 668~746MPa, tensile strength is 983~1035MPa, and total elongation A 80 The value is 11.0%~14.5%, the uniform elongation is 7.5%~12.0%, the yield strength ratio is 0.64-0.76, and the hole expansion rate is 35%~50%; the average grain size of the ferrite matrix is 1.6μm, the average grain size of the martensite is 1.0μm, and the average grain size of the tempered martensite is 1.2μm.
[0025] The C (carbon) element is an important element for stabilizing austenite and improving the strength of dual-phase steel. The carbon element mainly affects the volume fraction of austenite formed during annealing. The diffusion process of carbon in austenite or ferrite actually plays a role in controlling the growth of austenite grains. As the carbon content increases, the volume fraction of austenite increases, and then the martensitic phase structure formed after cooling increases, and the hardenability of martensite also increases, resulting in an increase in the strength of the material. At the same time, the plasticity of the material decreases, resulting in an increase in the hardness difference between the two phases. For steel parts with higher flanging and hole expansion requirements, the carbon content should not be too high. If the carbon content is too low, it will lead to insufficient hardenability, resulting in bainite transformation or insufficient strength, and other alloys need to be added to improve hardenability, resulting in increased alloy costs. Therefore, the C content (by weight percentage) of the present invention is 0.060%~0.095%, preferably 0.070%~0.090%.
[0026] The Si (silicon) element plays a significant role in solid solution strengthening in steel, and in the phase transformation process, effectively inhibits the precipitation of carbides, delays the transformation of pearlite, etc. When the critical zone is kept warm, Si has the effect of accelerating the diffusion of carbon elements into austenite, has a significant purification effect on ferrite, improves the purity of ferrite in dual-phase steel, promotes the formation of ferrite and expands the process window. On the other hand, too high a silicon content will increase the brittleness of martensite, resulting in poor toughness, and form high-melting-point oxides on the surface of the steel plate, which will affect the surface quality of the steel plate. It is necessary to control the silicon content at a certain level, which can not only play a role in strengthening ferrite but also not significantly reduce brittleness and surface quality. Therefore, the Si content (by weight percentage) of the present invention is: 0.30~0.80%, preferably 0.40%~0.55%.
[0027] Mn (manganese) element is a good deoxidizer and desulfurizer, and is also a commonly used solid solution strengthening element in steel. Mn can combine with C to form a variety of carbides to play a role in precipitation strengthening, and can also be dissolved in the matrix to enhance the solid solution strengthening effect. Mn is easy to combine with S to form a high melting point compound MnS, thereby eliminating or weakening the hot brittleness caused by FeS and improving the hot working performance of steel. Mn can improve the stability of austenite, shift the C curve to the right, and thus significantly reduce the critical cooling rate of martensite. However, when the Mn content is too high, it is easy to enrich the surface to form manganese oxides during the annealing process, thereby causing the surface quality to decrease. More importantly, the Mn content is too high and it is easy to cause segregation to form a banded structure, which increases the anisotropy of the material. Therefore, in the present invention, the Mn content (by weight percentage) is 1.95% to 2.45%, preferably 2.00% to 2.25%.
[0028] Cr (chromium) element is a medium-strong carbide-forming element. Like manganese, it can improve the hardenability of steel. When added to steel in combination with other alloying elements, it can greatly improve the hardenability of steel, thereby delaying pearlite transformation and bainite transformation, and expanding the coiling window. Cr is also a solid solution strengthening element, which plays a role in strengthening the matrix. On the other hand, too high Cr content will greatly improve the hardenability of steel, thereby greatly increasing the strength. Since Cr has obvious cost advantages over Mo, it is added to dual-phase steel in large quantities. However, Cr will also cause plasticity to decrease, deteriorating the forming performance and welding performance of steel. Therefore, the Cr content in the present invention is 0.55~0.85%, preferably 0.60%~0.80%.
[0029] The main role of Nb (nickel) element in steel is to refine grains. Nb atoms are relatively large in size and have a significant atomic dragging effect during hot rolling heating to inhibit the growth of austenite grains. During the finishing rolling process, Nb-containing second phases (NbC, NbN) are precipitated to pin grain boundaries to inhibit the coarsening of austenite, and Nb has a significant effect of inhibiting recrystallization. Nb is the most effective and easy-to-operate element for grain refinement. It only requires "low temperature and high reduction rate" to achieve grain refinement and is one of the most widely used microalloying elements. Nb mainly exists in the form of NbC in dual-phase steel, which has significant grain refinement and dispersion precipitation strengthening effects. During continuous annealing and heating, undissolved NbC particles can pin ferrite grain boundaries, thereby playing a role in refining grains. When the Nb content is too low, the grain refinement effect is not significant, but too high a Nb content will lead to a significant increase in alloy cost. Therefore, the Nb content in the present invention is 0.010~0.030%, preferably 0.015%~0.025%.
[0030] The Ti (titanium) element is mainly precipitation strengthened in steel, and combines with C and N in steel to form TiC and TiN, which plays a strong precipitation strengthening role and significantly refines the grains. The most important thing about Ti in B-containing steel is to fix the N element, so that the B element is in a solid solution state, and give full play to its effect of significantly improving hardenability. In addition, Ti has the effect of significantly inhibiting recrystallization and further refining the grains, but too high a Ti content will significantly increase the deformation resistance during the rolling process and increase the load of the cold rolling unit. On the other hand, high Ti is prone to form liquid TiN, and coarse liquid TiN will cause the plastic toughness of the material to deteriorate dramatically. Therefore, the Ti content in the present invention is 0.020~0.060%, preferably 0.040%~0.055%.
[0031] The Cu (copper) element has a good aging strengthening ability. The Cu nano-precipitates can effectively strengthen the ferrite. After the strip is annealed and cooled to a certain temperature, it needs to be kept warm, which can effectively produce the aging strengthening effect. In addition, the dispersion precipitation of Cu can inhibit the formation of coarse TiC and TiN, which plays a role in composite strengthening. However, too high Cu will increase the brittleness of the steel, and make the hot-rolled strip strength too high, and the edge cracks will be serious during cold rolling. Therefore, the content of the Cu element is set to 0.020~0.10%, preferably 0.030%~0.080%.
[0032] Al (aluminum) is a common deoxidizer in steel. It can also form AlN to pin the grain boundary, thereby refining the grains. In addition, Al has a similar effect to Si and can inhibit the precipitation of carbides, thereby making the austenite fully carbon-rich. When the Al content is low, it is difficult to remove the O element in the molten steel; when the Al content is too high, it is easy to generate a large amount of Al2O3 inclusions, which affects the cleanliness of the steel. Therefore, the Als content in the present invention is 0.02% to 0.07%, preferably 0.028% to 0.060%.
[0033] P (phosphorus) is an impurity element in steel, which is easy to segregate at the grain boundary and weaken the intercrystalline bonding force. During the rapid solidification process, a high P content is easy to cause cracking of the ingot. Therefore, in the present invention, the P content is ≤0.016%, preferably ≤0.012%.
[0034] S (sulfur) is an impurity element in steel, which is easy to be segregated at the grain boundary and form FeS with low melting point with Fe in steel, which reduces the toughness of steel and easily causes small micro cracks on the surface of the ingot during rapid solidification. Therefore, the S content in the present invention is 0.012%, preferably ≤0.008%.
[0035] The B (boron) element has the specific effect of improving hardenability and inhibiting recrystallization. B atoms are small and easily segregated at the grain boundaries, which greatly inhibits the progress of recrystallization. At the same time, it significantly increases the incubation period of pearlite and bainite, thereby improving hardenability. However, B easily combines with N to form BN, which cannot inhibit recrystallization and improve hardenability. Therefore, the B content in the present invention is 0.0010% to 0.0040%, preferably 0.0020% to 0.0035%.
[0036] N (nitrogen) element is an impurity element in steel. Due to its small atomic size, it is easy to enter the gap between iron elements, significantly improve lattice distortion and greatly increase strength, but it will significantly deteriorate the plasticity and toughness of steel. At the same time, N is easy to combine with Al, B, and Ti in steel to form second phases such as AlN, BN and TiN, while strengthening and deteriorating the plasticity and toughness of steel. Especially when the N content is too high, it combines with Ti to form liquid TiN, which can reach micron level. Not only does it not play a strengthening role, but it also causes stress concentration to form crack sources. The content of N element needs to be strictly controlled. Therefore, the N content in the present invention is ≤0.0060%, preferably 0.0035%.
[0037] A second aspect of the embodiments of the present invention provides a method for preparing a low-cost, high-hole expansion performance 980 MPa grade continuously annealed dual-phase steel, comprising the following steps: a. Smelting process: smelting the raw materials of duplex steel and forming slabs through continuous casting; b. Hot rolling process: The slab is heated, descaled, rough rolled, finished rolled and laminar cooled to obtain hot rolled coil; the final rolling temperature is 845℃-915℃; the laminar cooling adopts the front cooling method, the upper and lower surface cooling rates are 40%-60% and 65%-85%, and the coiling temperature is 525-565℃.
[0038] c. Pickling process: After the hot-rolled coil is pickled, it is formed into a hot-rolled plate coil, and then cold-rolled into a thin strip steel of 0.8-2.0 mm; wherein, the cold rolling reduction rate is 43%-68%; as the cold-rolled thickness of the material increases, the cold rolling reduction rate gradually decreases, and the thickness of the raw material is adjusted accordingly for every 0.3 mm increase in the thickness specification of the cold-rolled thin strip steel, and the cold rolling reduction rate is reduced by about 5~7%.
[0039] d. Continuous annealing process: The cold-rolled thin strip steel is continuously annealed to obtain low-cost, high-expansion performance 980MPa grade continuous annealing dual-phase steel; the cold-rolled thin strip steel is heated in stages to 300℃, 720℃ and 805~845℃, and the absorptive temperature gradually increases with the increase of the strip thickness, and the absorptive temperature increases by 10℃ for every 0.3mm increase in strip thickness. After keeping warm for 90-180s, it is slowly cooled to 660~680℃ at 1.7~7.8℃ / s, and then quickly cooled to 250℃~290℃ at a rate of 19~33℃ / s, wherein the slow cooling end temperature and over-aging temperature increase by 5℃ and 10℃ respectively for every 0.3mm increase in strip thickness, and cooled to room temperature after keeping warm for 400~760s. The unit speed is 95-135m / min. As the cold-rolled thickness of the material increases, the unit speed gradually slows down. The unit speed decreases by 10m / min for every 0.3mm increase in strip thickness. The flattening elongation range is 0.25~0.45%, and the flattening elongation decreases by 0.05% for every 0.3mm increase in material thickness.
[0040] Example This embodiment provides four groups of low-cost high hole expansion performance 980MPa grade continuous annealing dual-phase steels, namely, Examples 1-4, and Comparative Examples 1-2, whose chemical compositions are shown in Table 1; Table 1 Chemical composition of low-cost and high hole expansion performance 980MPa graded continuous annealing dual-phase steel (wt.%)
[0041] The specific process of the preparation method of the above-mentioned low-cost and high-hole expansion performance 980MPa grade continuously annealed dual-phase steel plate is as follows: A. Smelting process: After the smelting process, a dual-phase steel slab with the chemical composition shown in Table 1 is prepared; B. Hot rolling process: The slab is heated, descaled, hot rolled and laminar cooled to obtain a hot rolled coil. The specific hot rolling process parameters are shown in Table 2. Table 2 Main process parameters of hot rolling of 980MPa annealed dual-phase steel with low cost and high hole expansion performance serial number Final rolling temperature / ℃ Coiling temperature / ℃ Cooling method Cooling rate of upper and lower headers ℃ / s Example 1 883 548 Front cooling 50%、75% Example 2 875 552 Front cooling 50%、75% Example 3 868 540 Front cooling 50%、75% Example 4 876 555 Front cooling 50%、75% Comparative Example 1 930 585 Front cooling 50%、75% Comparative Example 2 850 500 Front cooling 50%、75% C. Pickling process: After the hot-rolled coil is pickled, it is cold-rolled into thin strip steel. The hot-rolled plate thickness, cold-rolled plate thickness and cold-rolling reduction ratio are shown in Table 3.
[0042] Table 3 Cold-rolled raw materials, finished products and reduction ratio of 980MPa graded annealed dual-phase steel with low cost and high hole expansion performance serial number Hot rolled plate thickness / mm Cold rolled sheet thickness / mm Cold rolling reduction rate / % Example 1 3.10 1.40 55 Example 2 3.50 2.00 43 Example 3 3.33 1.70 49 Example 4 2.82 1.10 61 Comparative Example 1 3.10 1.40 55 Comparative Example 2 3.10 1.40 55 D. Continuous annealing process: The cold-rolled thin strip is heated in sections to 300℃, 720℃ and 805~845℃. The ambulation temperature increases gradually with the increase of the strip thickness. The ambulation temperature increases by 10℃ for every 0.3mm increase in strip thickness. After keeping warm for 90-180s, it is slowly cooled to 660~680℃ at 1.7~7.8℃ / s, and quickly cooled to 250℃~290℃ at a rate of 19~33℃ / s. The slow cooling end temperature and over-aging temperature increase by 5℃ and 10℃ respectively for every 0.3mm increase in strip thickness. After over-aging keeping warm for 400~760s, it is cooled to room temperature. The unit speed is 95-135m / min. The unit speed gradually slows down with the increase of the cold-rolled thickness of the material. The unit speed decreases by 10m / min for every 0.3mm increase in strip thickness. The flattening elongation range is 0.25~0.45%, and the flattening elongation decreases by 0.05% for every 0.3mm increase in material thickness. The specific continuous annealing process parameters are shown in Table 4: Table 4 Main annealing process parameters of 980MPa grade annealed dual-phase steel with low cost and high hole expansion performance
[0043] The microstructure of the low-cost and high-hole expansion performance 980MPa graded continuous annealing dual-phase steel prepared by the above process is as follows: Figure 1 to Figure 2 The stress-strain curve is shown in Figure 3 The above continuous annealing dual-phase steel properties are tested according to GB / T228-2010 "Room Temperature Tensile Test Method for Metallic Materials", as shown in Table 5: Table 5 Properties of 980MPa graded continuous annealing dual-phase steel with low cost and high hole expansion performance
[0044] It can be seen that the hole expansion rate of Examples 1-4 can be maintained at about 40% while maintaining good yield strength, tensile strength, uniform elongation, and yield strength ratio. Although the hole expansion rate of Comparative Example 1 is similar to that of Examples 1-4, the yield strength and tensile strength are significantly lower. The uniform elongation, yield strength, and hole expansion rate of Comparative Example 1 are all lower than those of Examples 1-4.
[0045] The alloy content of Comparative Example 1 is low, resulting in its strength significantly lower than 980MPa. Comparative Example 2 adds more C, Mn, Cr and other elements, and the hardenability is significantly increased. Its tensile strength reaches 1123MPa, but the plasticity (only 7.7%) and hole expansion rate (only 26%) are greatly reduced. At the same time, the addition of C element will deteriorate the welding performance.
[0046] The above are exemplary embodiments disclosed in the present invention, but it should be noted that various changes and modifications may be made without departing from the scope of the embodiments disclosed in the claims. Although the elements disclosed in the embodiments of the present invention may be described or required in individual form, they may also be understood as multiple unless explicitly limited to the singular.
[0047] A person skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the disclosure of the embodiments of the present invention (including the claims) is limited to these examples; under the concept of the embodiments of the present invention, the technical features in the above embodiments or different embodiments can also be combined, and there are many other changes in different aspects of the above embodiments of the present invention, which are not provided in detail for the sake of simplicity. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present invention should be included in the protection scope of the embodiments of the present invention.
Claims
1. A low-cost, high-hole expansion performance 980MPa grade continuous annealing dual-phase steel, characterized in that: The chemical composition of the dual-phase steel includes, by weight percentage, C: 0.060%-0.095%, Si: 0.30%-0.80%, Mn: 1.95%-2.45%, Cr: 0.55%-0.85%, Nb: 0.010%-0.030%, Ti: 0.020%-0.060%, Cu: 0.020%-0.10%, P≤0.016%, S≤0.012%, Als: 0.02%-0.07%, N≤0.0060%, B: 0.0010%-0.0040%, and the remaining elements are Fe and unavoidable impurities.
2. The low-cost and high-hole expansion performance 980MPa grade continuously annealed dual-phase steel according to claim 1, characterized in that: The invention discloses a low-cost and high-hole expansion performance 980MPa grade continuously annealed dual-phase steel. The chemical composition of the dual-phase steel comprises, by weight percentage, C: 0.070%-0.090%, Si: 0.40%-0.55%, Mn: 2.00%-2.25%, Cr: 0.60%-0.80%, Nb: 0.015%-0.025%, Ti: 0.040%-0.055%, Als: 0.028%-0.060%, Cu: 0.030%-0.080%, P≤0.012%, S≤0.008%, N≤0.0035%, B: 0.0020%-0.0035%, and the balance is Fe and unavoidable impurities.
3. The low-cost and high-hole expansion performance 980MPa grade continuously annealed dual-phase steel according to claim 1, characterized in that: The microstructure of the dual-phase steel is composed of 42%-47% ferrite, 30%-35% martensite and 18%-28% tempered martensite, and its yield strength is 668-746MPa, tensile strength is 983-1035MPa, and total elongation A 80 The value is 11.0%~14.5%, the uniform elongation is 7.5%~12.0%, the yield strength ratio is 0.64-0.76, and the hole expansion rate is 35%~50%; the average grain size of the ferrite matrix is 1.6μm, the average grain size of the martensite is 1.0μm, and the average grain size of the tempered martensite is 1.2μm.
4. A method for preparing low-cost high hole expansion performance 980MPa grade continuously annealed dual-phase steel as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: a. Smelting process: smelting the raw materials of duplex steel and forming slabs through continuous casting; b. Hot rolling process: The slab is subjected to heating, descaling, rough rolling, finish rolling and laminar cooling to obtain a hot rolled coil; c. Pickling process: After the hot-rolled coil is pickled, it is formed into a hot-rolled coil, and then cold-rolled into a thin strip steel of 0.8-2.0 mm; wherein, the cold rolling reduction rate is 43%-68%; d. Continuous annealing process: The cold-rolled thin strip steel is continuously annealed to obtain low-cost, high-hole expansion performance 980MPa grade continuous annealing dual-phase steel; wherein the cold-rolled thin strip steel includes a three-stage graded heating and a three-stage cooling process; wherein the three-stage cooling process includes: the annealing temperature is 805-845°C, first slowly cooled to 660-680°C at 1.7-7.8°C / s, then quickly cooled to 250-290°C at 19-33°C / s, and finally cooled to room temperature.
5. The method for preparing low-cost high hole expansion performance 980MPa grade continuously annealed dual-phase steel according to claim 3, characterized in that: In the step b, the final rolling temperature is 845°C-915°C.
6. The method for preparing low-cost high hole expansion performance 980MPa grade continuously annealed dual-phase steel according to claim 3, characterized in that: In the step b, the laminar cooling adopts the front-stage cooling method, the cooling rates of the upper and lower surfaces are 40%-60% and 65%-85% respectively, and the coiling temperature is 525-565°C.
7. The method for preparing 980MPa grade continuously annealed dual-phase steel with low cost and high hole expansion performance according to claim 3, characterized in that: In the step d, the unit speed is controlled at 95-135 m / min according to the thickness of the strip steel; wherein, for every 0.3 mm increase in the thickness of the strip steel, the unit speed is reduced by 10 m / min.
8. The method for preparing low-cost high hole expansion performance 980MPa grade continuously annealed dual-phase steel according to claim 3, characterized in that: In the step a, the following raw materials of the dual-phase steel are smelted: in terms of weight percentage, the chemical composition of the dual-phase steel includes: C: 0.060%~0.095%, Si: 0.30~0.80%, Mn: 1.95%~2.45%, Cr: 0.55~0.85%, Nb: 0.010~0.030%, Ti: 0.020~0.060%, Cu: 0.020~0.10%, P≤0.016%, S≤0.012%, Als: 0.02%~0.07%, N≤0.0060%, B: 0.0010%~0.0040%, and the remaining elements are Fe and unavoidable impurities.
9. The method for preparing low-cost high hole expansion performance 980MPa grade continuously annealed dual-phase steel according to claim 3, characterized in that: In step d, the three-stage graded heating process includes: the first stage is a preheating stage with an outlet temperature of 300°C; the second stage is a heating stage, heating the strip to 720°C; and the third stage is a heating stage 2, heating the strip to 805-845°C.
10. The method for preparing low-cost high hole expansion performance 980MPa grade continuously annealed dual-phase steel according to claim 3, characterized in that: In the step d, the flattening elongation ranges from 0.25 to 0.45%, and the flattening elongation decreases by 0.05% for every 0.3 mm increase in the thickness of the dual-phase steel.